(untitled) (Economics and region, 2024)
The article analyzes the changes that have occurred in the dynamics of attracting foreign direct investment (FDI) to the regions of Ukraine due to the outbreaks of the war. The issue of uneven regional distribution of foreign capital in previous years aroused great interest on the part of domestic academic economists in the context of imbalances in the level of economic development of regions. Particular attention in this study is paid to a comprehensive review of the work of these researchers from the point of view of the conditions in which the regions found themselves with the outbreak of a full-scale war in Ukraine. One notable consequence of this conflict has been a significant change in the stock and flow of foreign direct investment. If previously their distribution among regions was determined, first of all, by the geographical location of the regions, the development of their economic and industrial potential, transport infrastructure, and human capital, then with the beginning of the war, the impact of these factors weakened significantly. The factors of remoteness from the active warzone and the extent to which the region’s economy suffered from the consequences of the war began to play a much larger role in the investment attractiveness of regions. Taking this into account, a scientifically based assessment of the strength of influence of these factors on the dynamics of the regional distribution of FDI and their structure was chosen as the primary objective of the study. The results obtained through the use of advanced economic statistics methods made it possible to identify key relationships and trends within the mentioned processes. In particular, it was possible to establish the degree of differentiation of the impact of the war’s consequences on various elements of FDI flows by region, which constitutes the scientific novelty of the presented research. At the same time, the results of the work have practical significance, since they can be used to develop effective strategies to attract investment and restore the affected regions of Ukraine. The findings provide valuable insights for policymakers and stakeholders involved in the economic recovery and development of the war-impacted areas.